2023
DOI: 10.3390/antiox12122066
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed and Seaweed-Based Functional Metabolites as Potential Modulators of Growth, Immune and Antioxidant Responses, and Gut Microbiota in Fish

Muhammad A. B. Siddik,
Prue Francis,
Md Fazle Rohani
et al.

Abstract: Seaweed, also known as macroalgae, represents a vast resource that can be categorized into three taxonomic groups: Rhodophyta (red), Chlorophyta (green), and Phaeophyceae (brown). They are a good source of essential nutrients such as proteins, minerals, vitamins, and omega-3 fatty acids. Seaweed also contains a wide range of functional metabolites, including polyphenols, polysaccharides, and pigments. This study comprehensively discusses seaweed and seaweed-derived metabolites and their potential as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 206 publications
(168 reference statements)
0
0
0
Order By: Relevance
“…Additionally, certain seaweed compounds, like polysaccharides may promote gut health, enhancing overall digestion and nutrient absorption [ 82 , 83 ]. However, the specific impact can vary depending on the type and amount of seaweed, as well as the fish species involved [ 15 , 84 ]. For instance, several studies have demonstrated that the green seaweed Ulva spp , when included at levels of up to 5%, can enhance the growth performance of certain carnivorous fish [ 85 , 86 ], and omnivorous fish like tilapia of up to 20% of inclusion [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, certain seaweed compounds, like polysaccharides may promote gut health, enhancing overall digestion and nutrient absorption [ 82 , 83 ]. However, the specific impact can vary depending on the type and amount of seaweed, as well as the fish species involved [ 15 , 84 ]. For instance, several studies have demonstrated that the green seaweed Ulva spp , when included at levels of up to 5%, can enhance the growth performance of certain carnivorous fish [ 85 , 86 ], and omnivorous fish like tilapia of up to 20% of inclusion [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indonesia's role and strategic position in the global seaweed arena is very vital. Along with the increase in basic demand for seaweed-based colloids and various other derivative products that are concerned with the issue of back to nature (Khan et al, 2024;Shukla et al, 2021;Siddik et al, 2023). Indonesia is an archipelagic country that has the potential for 26 million hectares of marine and coastal fishery areas.…”
Section: Introductionmentioning
confidence: 99%
“…Insects, particularly black soldier fly larvae and mealworms, have been recognized for their high protein content and efficiency in converting low-value organic waste into high-quality protein. This not only addresses the need for sustainable protein sources but also contributes to waste reduction [16][17][18]. Single-cell proteins, encompassing yeast, algae, and bacterial proteins, represent another innovative avenue.…”
Section: Introductionmentioning
confidence: 99%